Aspectos psicossociais na vivência do ninho vazio em mulheres: uma compreensão da psicologia analítica - Ferreira, Tatiana Lima (2012)
This research seeks to observe and to understand feelings and behaviors of mothers in "empty nest" phase. The theme is justified mainly because it is an intrinsic step to the family cycle and not much exploited so far in Brazilian scientific research. So it has importance both in academia and to women demonstrated suffering at this stage. Using a qualitative approach, the study was used of questionnaire socio-demographic and semi-open interview, besides having been based on concepts of Analytical Psychology. It is considered that the majority of mothers interviewed showed negative reaction to the departure of the children, with feelings of sadness, loneliness, grief and abandonment. We conclude that the quality of the marital relationship and family that the mother established throughout her life may have influenced the type of reaction experienced at empty nest stage